Performance of Serum CA125 as a Prognostic Biomarker in Patients With Uterine Papillary Serous Carcinoma. Issue 3 (1st April 2011) - Gupta, Divya; Gunter, Marc J.; Yang, Kathleen; Lee, Stephen; Zuckerwise, Lisa; Chen, Lee-may; Goldberg, Gary L.; Huang, Gloria S.
Abstract : Hypothesis: Serum CA125 is a potential biomarker for metastatic disease and recurrence in patients with uterine papillary serous carcinoma (UPSC). Methods: All patients with UPSC who had preoperative CA125 measurement and surgical staging between 1998 and 2008 at the participating institutions were included in this analysis (N = 52). Data were extracted from patients' records. Fisher exact and χ 2 tests were used to assess the association of CA125 levels with clinical and pathological variables. The correlation between CA125 levels (high/low) and lymph node metastases (positive/negative) was evaluated using Spearman correlation coefficients. The association of CA125 elevation with recurrence-free survival was assessed using Cox proportional hazards regression modeling. Results: Preoperative CA125 elevation (>30 U/mL) was observed in 9 (17%) patients and was associated with advanced International Federation of Gynecologists and Obstetricians (FIGO) stage III/IV disease ( P = 0.002), lymph node involvement ( P = 0.007), and presence of omental metastases ( P = 0.001). Disease recurrence and survival data were available for 51 of the 52 patients. During a mean follow-up time of 36 months, 15 (29%) patients experienced disease recurrence and 10 (19%) patients died. There was a moderate positive correlation between CA125 levels and lymph node metastases ( r 2 = 0.39). On multivariate survival analysis, an elevated CA125 level compared to nonelevated CA-125 was not associated with disease recurrence (hazard ratio, 1.61; 95% confidence interval, 0.55-4.77). Conclusions: Preoperative CA125 levels were significantly associated with metastatic disease in patients with UPSC. However, in this study of surgically staged UPSC patients, preoperative CA125 elevation was not an independent predictor of disease recurrence.